(3GdYde GdWHjYjs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s; (3OGhO GdGfWGcj , OGhO Hf YeQ GdHUjQ GdGfWGcj,J (B1008 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI(B: (3PcQ GdeDda bUOfG aj gPG GdcJGH gh Cf fXgQ MceI Gddg JYGdj PcQg aj Ndb GdEfSGf hfHKg Ydj ahGjO dWjaI TQjaI de jSHbfG Edj eYQaJgG s
(3BNQgG (B:s
(3hLYd GdKOi GKfjf Ydi YOO HWhf GdQMe ZjQ GdUOQ , hbY Nd heTbI ai eYfi GdEQVGY hGdEQJVGY JeJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B160 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(237) s
Keywords: (3GdWHs